ELECTROCHEMISTRY APPLICATIONS FOR SUSTAINABLE ENERGY - Huang, Wendy (My University, 2017)
While the terms reduce, reuse, and recycle are common concepts in minimizing resource waste, most people do not think twice about energy as a resource or the large amounts of wasted energy in wastewater treatment and industrial processes. Recovery of wasted energy or reducing the net energy consumption of such processes would save resources and reduce energy costs. This research investigated emerging energy systems for handling wastewater (bioelectrochemical systems) and waste heat (ion exchange membrane systems) to elucidate and quantify thermodynamic and kinetic phenomena in biological and electrochemical reactions. Bioelectrochemical systems utilize exoelectrogenic microorganisms for wastewater treatment energy recovery in the form of electricity or biogas. The substrate utilization and electron transfer by exoelectrogens to the bioanode have not been clearly explained and thus there are no commonly accepted models for bioanode performance. A comprehensive model for bioanode operation was proposed including equilibrium, kinetics, and microbiological characteristics. The utilization and preference of different organic substrates were also assessed with electrochemical techniques and it was found that linear sweep voltammetry and exchange current are good indicators of whether a substrate is directly or indirectly utilized by exoelectrogenic microorganisms. This research also investigated ion exchange membrane systems for energy recovery from waste-grade heat, such as that wasted in the steel refinery and power industries, using concentration gradients of ammonium bicarbonate solutions. Estimation of the junction potential (amount of concentration gradient energy) has significant technical difficulties for highly concentrated ammonium bicarbonate solutions (e.g., unknowns in equilibrium speciation and activity coefficient determination). A straightforward estimation method was proposed and found to be able to reliably determine the junction potential across an ion exchange membrane based on conductivity measurement, simplifying the model for junction potential determination.
Keywords: Bioelectrochemistry; Energy; Sustainability; Junction Potential; Wastewater; Resource Recovery